Pengaruh Gaya Kepemimpinan Transformasional dan Pengembangan Karir Terhadap Kinerja Karyawan pada PT. Paes Entertaiment (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This research is quantitative research, where this study aims to determine the influence of transformational leadership style and career development on employee performance. The sample used in this study was 100 respondents from all employees of PT. Paes Entertainment. Instrument testing is carried out through validity and reliability tests where all respondents in this test are said to be valid. The data analysis methods used are statistical description, multiple analysis and hypothesis testing where to determine the magnitude of the influence a determination test is used.  The results of this study. The results showed that, H₁ is accepted which means transformational leadership has a positive effect on employee performance. H₂ is accepted which means career development has a positive effect on performance. H₃ is accepted which means the variables of transformational leadership and career development together have a positive effect on employee performance